PRAGMATISM-ACCOMMODATIVE POLITICAL PATTERNS OF AL-IRSYAD DURING THE REIGN OF PRESIDENT SOEKARNO, 1945-1965 - Miftahuddin, Miftahuddin; Abdurahman, Dudung (State Islamic University (UIN) of Sunan Ampel Surabaya, 2023)
This article examines the roles and political behaviors of Al-Irsyad during the President of Soekarno's reign (1945-1965).This study is part of an effort to complete the history of Al-Irsyad's journey which seems to have not been revealed by academics, the role and political attitude of Al-Irsyad in the era of President Soekarno in particular. Using historical research methods supported by the main primary sources that have not been explored by scholars, such as a collection of writings welcoming the